Guanaco colonisation of Tierra del Fuego Island from mainland Patagonia: Walked, swam, or by canoe? - William L. Franklin (Geo: Geography and Environment, 2022)
Abstract Addressed here is the biogeographical‐vexing question of why the guanaco (Lama guanicoe) is the only large mammal on the big island of Tierra del Fuego, answered by comparing alternative colonisation hypotheses. A multidisciplinary examination was conducted into the archaeological, ecological, evolutionary, geographical, genomic, glacial and zoological past, plus distribution of native terrestrial vertebrates in the Patagonia of southern South America. Notable disparities exist between main Patagonia (2.5 species/10,000 km2) compared with Tierra del Fuego (1.8). In the similar‐sized area of mainland Patagonia just north of the Strait of Magellan there are 12 reptiles, 7 amphibians and 34 mammals = 53 total species; Tierra del Fuego has 13. Despite being the size of Switzerland and only 3.1 km from the mainland, Tierra del Fuego has no species of snakes, salamanders, frogs or turtles, only one lizard, one toad, nine small mammals, one carnivore and one ungulate, the Guanaco. An innovative proposal is made contrary to traditional thinking: Tierra del Fuego has relatively few native‐terrestrial vertebrates because they were decimated by major tephra‐ash fallout (2 to >15 cm) from the Holocene 7750 YBP (years before present) Hudson volcano, the biggest and most destructive eruption in Patagonia during the past 10,000 years that eradicated indigenous peoples, most terrestrial vertebrates and all Guanacos. Neither terrestrial vertebrates nor man were replenished from the adjacent mainland for 1000 years because the Strait of Magellan was a complete biogeographical barrier. Guanacos on Tierra del Fuego have lower genetic diversity compared with the mainland, suggesting it is a younger population. Empirical evidence and pivotal events of Patagonia's prehistory support one of three hypotheses: guanacos were introduced to Tierra del Fuego by early Holocene, guanaco‐dependent, indigenous peoples from the mainland who repopulated Tierra del Fuego utilising the newly invented, skilfully crafted, seaworthy bark canoe (Appendix S1–Resumen en Español).